(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: The purpose of this research is to evaluate the diagnostic accuracy of arthroscopic findings versus a 0.3-tesla MRI for meniscal damage in the knee. Methodology: Eighty individuals were sent from the orthopaedic clinic who met the inclusion criteria for the study. This 0.3 Tesla scan was done by just one MRI technician. A professor of orthopedics performed an arthroscopy to corroborate the MRI’s findings. Using a proforma spreadsheet, we recorded and examined all of the information.00 Results Out of the total, 72 were males (or 90%) and 8 were females (or 10%). Mean age of the cases was 27.16 years. Contrary to arthroscopy, MRI was more sensitive (98%), specific (94%), and accurate (96%), when it came to identifying meniscal lesions of the knee joint. Conclusion: We found that magnetic resonance imaging (MRI) is a safe, accurate, and noninvasive way to assess meniscal injuries.